If it is given
∫ − ∞ ∞ x 6 − 2 x 5 − 2 x 4 + 4 x 3 + 3 x 2 − 4 x + 1 x 2 d x = π ,
then the value of
∫ 0 ∞ x 1 2 − 1 0 x 1 0 + 3 7 x 8 − 4 2 x 6 + 2 6 x 4 − 8 x 2 + 1 x 8 − 4 x 6 + 9 x 4 − 5 x 2 + 1 d x
can be expressed as q p π . Find the value of p 2 + q 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It appeared first in AMM. See the solution using complex analysis by this mathematician: the integral
Problem Loading...
Note Loading...
Set Loading...
Let
g ( x ) f ( x ) = x 6 − 2 x 5 − 2 x 4 + 4 x 3 + 3 x 2 − 4 x + 1 x 2 = x 1 2 − 1 0 x 1 0 + 3 7 x 8 − 4 2 x 6 + 2 6 x 4 − 8 x 2 + 1 x 8 − 4 x 6 + 9 x 4 − 5 x 2 + 1
They are related as
f ( x ) = 2 g ( 1 + x ) + g ( 1 − x )
∴ ∫ 0 ∞ f ( x ) d x = 2 1 ( ∫ 0 ∞ g ( x ) d x + ∫ 0 ∞ g ( − x ) d x ) = 2 1 ( ∫ 0 ∞ g ( x ) d x + ∫ − ∞ 0 g ( x ) d x ) = 2 1 ∫ − ∞ ∞ g ( x ) = 2 π
Hence, enter 5.